A Comparative Study of EmberGen and Blender in Fire Explosion Simulations - Arya Luthfi Mahadika; Ema Utami (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
The advancement of visual effects (VFX) technology has intensified the need for efficient fire explosion simulations across film, gaming, and real-time applications. This study investigates and compares the performance of two prominent simulation tools—EmberGen and Blender—by focusing on processing time efficiency and simulation quality. The research specifically evaluates five critical simulation aspects: fire particle generation, smoke behavior, turbulence effects, light dispersion, and final rendering (finishing). A total of five professional VFX artists conducted five separate tests using each software, generating a comprehensive dataset for analysis. Results show that EmberGen achieves a 29.91% overall improvement in simulation speed compared to Blender, with significant gains in fire particle generation (38.5%), smoke simulation (42.3%), turbulence effects (15.7%), light dispersion (8.9%), and finishing (11.6%). These findings indicate that EmberGen is highly effective for real-time or rapid-turnaround projects, while Blender remains advantageous for detailed, high-fidelity simulations in cinematic contexts. The study concludes that software selection should be driven by project-specific demands, where EmberGen supports time-sensitive production workflows and Blender offers greater artistic control. This research underscores the critical need for aligning simulation tools with both creative goals and production efficiency, contributing to decision-making in VFX, animation pipelines, and educational training environments within the information systems and digital content domains.